Isolepis R.Br. (Cyperaceae) revisited : a phylogeny based on plastid and nuclear ribosomal DNA data - Wiswedel, Stefan (Department of Biological Sciences, 2023)
The approximately 75 species of Isolepis R Br. are currently described as annual or short lived perennials with predominantly terete spikelet's